Zapalenie tkanki podskórnej jako rzadki objaw kliniczny genetycznie uwarunkowanych zaburzeń α1-antytrypsyny - przegląd piśmiennictwa - Agata Maciejewska-Radomska; Aleksandra Wilkowska (Termedia Publishing House, 2011)
α1-Antitrypsin (AAT) is a serine protease inhibitor responsible forregulating proteinases' activity in the blood. α1-Antitrypsin deficiencyis a result of SERPINA 1 gene mutation and it is one of the most commongenetic abnormalities in Caucasians. There are over 130 different alleles for this gene. Some of them are responsible for low AAT levelsin the serum, while other variants encode defective glycoproteins -functionally impaired.Patients with decreased AAT serum level are at high risk of seriouspulmonary diseases (chronic pulmonary obstructive disease, asthmabronchiale, emphysema) or liver cirrhosis. On the other hand, it shouldbe mentioned that there is a possibility of systemic life-threateningsymptoms in patients with the mutated AAT gene and normal AATlevels.Panniculitis is one of the rarest manifestations of AAT deficiency. Thedisease is characterised by a typical clinical picture with deep, painfulinflammatory infiltrations, ulcerations, fistulas and oily liquid. It maydevelop in a patient with a mutated gene and concomitant decreased ornormal AAT level.In this article, particular attention is paid to the diagnostic aspects ofSERPINA 1 gene mutations, especially in patients who have a mutatedgene with a normal level of α1-antitrypsin in the serum.